Respuesta :

Answer:

(0,-1)

Step-by-step explanation:

:)

Answer:  (0, -1)

========================================================

Explanation:

The notation [tex](x,y) \to (x-6, y-1)[/tex] means that whatever the x coordinate is, we subtract 6 from it. At the same time, whatever the y coordinate is, we subtract 1 from it.

The point (x,y) = (6,0) means x = 6 and y = 0.

Therefore,

[tex](x,y) \to (x-6, y-1)\\\\(6,0) \to (6-6, 0-1)\\\\(6,0) \to (0, -1)[/tex]

Visually, the starting point (6,0) moves 6 units to the left and 1 unit down to arrive at (0,-1). See the diagram below.

Ver imagen jimthompson5910